Thermo-economic evaluation of a new approach to extract sugarcane wax integrated to a first and second generation biorefinery. (December 2018) - Albarelli, Juliana Q.; Santos, Diego T.; Meireles, M. Angela A.
Abstract: This study evaluates the integration of supercritical fluid extraction process to obtain sugarcane wax extract from the sugarcane filter cake residue. This cake is eliminated from the decantation process of sugarcane juice in the sugarcane biorefinery and it is generally used as a fertilizer. From this cake a lipophilic material, containing long-chain fatty alcohols and phytosterols, can be selectively recovered by means of the use of supercritical CO2 as extracting solvent. Aspen Plus ® software was used to simulate the sugarcane biorefinery producing electricity, conventional and cellulosic ethanol and wax extract. A thermal-economic model was developed in Matlab software to perform energy integration and the economic analysis of this novel biorefinery concept. The results showed that by increasing temperature and pressure of the extraction process it is possible to produce more wax extract at an overall lower investment as lower extraction time is necessary, decreasing the number of extractors working in parallel. The integration of the extraction process to the sugarcane biorefinery had no impact on the overall ethanol production and had small impact on the electricity available for sale to the grid, decreasing only around 3% the net electricity. Payback time is strongly reduced by this integration strategy, decreasing 74% when the best configuration for SFE is adopted. The selling price for the wax extract strongly influences on the economic viability of this process, indicating that the integration of this extraction process to the sugarcane biorefinery is only economic attractive if the wax extract selling price is higher than 26.5 USD/kg. Graphical abstract: Highlights: Development of a novel supercritical fluid-based sugarcane biorefinery concept. Use of CO2 rich off-gases generated from a biorefinery to extract phytochemicals. Synergy between supercritical CO2 extraction and sugarcane biorefinery. Use of heat, electricity and CO2 generated from a sugarcane biorefinery.